Health Literacy and Self-care Behavior during COVID-19 Pandemic - Mahdi Gholian-Aval; Fatemeh Pourhaji; Rasoul Raesi; Mohammad Hossein Delshad; Fahimeh Pourhaji; Khaled Samiee Roudi; Ali Vafaee Najar; Zeynab Zirak Marjaneh (Universidade Estadual de Maringá, 2024)
The Coronavirus is a large family of viruses that can cause respiratory infections. During the COVID-19 pandemic, there are many challenges, including the health literacy (HL) of society. On the other hand, self-care is a multidimensional structure that requires other behaviors influenced by factors such as health beliefs, economic situations and life events. The aim of the study was to determine the relationship between health literacy and self-care behaviors in the prevention of COVID-19 among the citizens of the city of KHAF. This cross-sectional study was conducted on 300 citizens aged 18 to 65 years in KHAF cities selected through a stratified random sampling method in the first half of 2021. The data collection tool was a questionnaire containing demographic information, health literacy (HL), and self-care questionnaire in the prevention of COVID-19. Data were analyzed using SPSS software and independent samples t-tests, one-way analysis, Pearson's correlation coefficient. The statistical significance level was set at p≤0.05. The results showed that the mean age of the participants was 32.32 ± 8.03 years. The results of the Pearson correlation test showed there was a significant and positive relationship between HL and self-care behavior (r=0.43, p≤0.001). HL had a positive relationship with self-care behaviors in the prevention of COVID-19 which requires further research and provides an incentive to develop and test special educational interventions at the level of HL to improve self-care in the prevention of COVID-19.